Seasonal periodicity of melatonin exchange and hormonal status of pregnant women in dependence on fetus sex - T. L. Botasheva; A. V. Khloponina; V. V. Vasil'eva; O. P. Zavodnov; L. V. Kaushanskaya; E. V. Zheleznyakova (Медицинский вестник Юга России, 2018)
Objective: to study melatonin metabolism and hormonal status of pregnant women in different seasons of the year, depending on the sex of the fetus. Materials and methods: 538 women were examined at the time of physiological gestation of 37-40 weeks. The first group — 286 pregnant women with female fetuses and the second group — 254 pregnant with male fetuses. Estimation of the hormonal status included the determination of the level of cortisol, estradiol, adrenocorticotropic hormone, progesterone, testosterone in the blood and melatonin in the urine of pregnant women. Results: the level of 6-sulphatoxymelatonin in the morning urine, regardless of the sex of the fetus, was higher in the seasons of the year with the predominance of the dark time of the day. Absolute levels of 6-sulphatoxymelatonin in urine in all women in 37-40 weeks of gestation were the lowest in the light-saturated summer and spring months of the year, while in the winter period its parameters were maximal. Melatonin production was statistically significantly higher in pregnant women with female fetuses during the fall and winter periods of the year. Regardless of the time of the year, in pregnant women with female fetuses, the absolute levels of estradiol and progesterone were higher than in the case of the male fetus. The highest values in the case of the female fetus were noted in the spring. Testosterone production was significantly higher in pregnant women with male fetuses mainly in the spring season. Stress resistance of pregnant women was higher in the summer months. Depending on the “sex of the fetus” factor, stress hormones in the summer had the highest values in pregnant women with male fetuses. Conclusions: the sex of the fetus is a significant factor affecting the seasonal variability of melatonin production, sexual and stress hormones in pregnant women due to the formation of the specificity of the systemic signaling between the maternal and the fetal organism in the dynamics of pregnancy.